Possibilities of Introduction of Automated Operation on the Prague Metro - Široký, Jaromír; Nachtigall, Petr; Tischer, Erik; Magdechová, Katarína (Kaunas University of Technology, 2018)
The issue of automated metro is a modern trend in rail transport. Its utilization is still mainly in the field of urban underground railways. This article shows the possibilities that the Prague Metro has in its expansion of the D line in the area of automatic operation. As a sub-part, the possibility of switching the current operation to automatic in the modification of the security equipment and new vehicles, was also solved. However, this option seems complex and inefficient. This article focuses on automated metro operation systems, their basic requirements and functions. There is also a definition of various degrees of automation and a description of differences in functions of individual types. This article gives also a basic overview of functions, which are necessary for an automated metro operation system. In the second part, the article provides for an analysis of automated metro systems in the world. The last part deals with various types of interlocking systems for the automated metro operation system, including their basic functions.
Možnosti zavedení automatizovaného řízení pražského metra
Keywords: automated metro; operation systems; rail transport; vehicles; basic functions.; automatické metro; operační systém; železniční doprava; dopravní prostředek; základní funkce.